WIDEBAND TEMPORAL CHANNEL MODEL USING POLAR CODES AND CONVOLUTIONAL CODES AT 26 GHz - Reni Dyah Wahyuningrum; Udlhiya , Ida (PPM Telkom University, 2025)
The rapid advancement of technology today is evident in fields such as wireless communication. Channel coding plays a crucial role in wireless communication systems because it is essential for mitigating errors and detecting them, thereby ensuring that the system’s performance meets the standards set by 5G technology. This study evaluates the Bit Error Rate (BER) performance in a Wideband Temporal/Statistical Spatial Channel Model (SSCM) using both polar and convolutional codes. The transmission system operates at a frequency of 26 GHz. The simulations for this research were conducted using Binary Phase Shift Keying (BPSK) modulation, with the simulation software utilized for testing. Additionally, the weather parameters for the city of Medan, obtained from the Meteorology, Climatology, and Geophysics Agency (BMKG), including rainfall, air temperature, humidity, and pressure. The power delay profile showed 13 paths, and the BER vulnerability at for the polar code was found to be 3.23%. The results indicate that the polar code outperformed the convolutional code in terms of BER performance, as the polar code achieved a lower Signal-to-Noise Ratio (SNR) compared to the convolutional code